Intellicorps - Ang, Qi Jun (2016)
INTELLICORPS is a 3D animation film portrayed in a form of advertisement. The first pharmaceutical company to produce “NEW ME”, an empty vessel to replace the original human body. The product “NEW ME” provide user the choice to augment his/her body parts.